THE EFFECT OF ORGANIZATIONAL SUPPORT AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE JOB SATISFACTION AT IMPERIAL KITCHEN RESTAURANT AND DIMSUM OUTLET BRANCH TANGERANG SELATAN - Sari, Riski Ulan; Soemadi, Rd Roro Anggraini (Universitas Muhammadiyah Tangerang, 2024)
The purpose of this study was to determine the effect of Organizational Support and Organizational Commitment on Employee Job Satisfaction partially or simultaneously at Imperial Kitchen Restaurant and Dimsum Outlet Branch, South Tangerang. The research method used is descriptive and associative methods. The population in this study amounted to 60 employees. The sampling technique was purposive sampling method, then used a saturated sample. The data analysis method used is multiple linear regression analysis. The results showed that the t-count value was 7.505 with a t-table value of 2.00172 which means there is a positive and significant influence between Organizational Support on Employee Job Satisfaction, the t-count value is 7.652 with a t-table value of 2.00172 which means there is a positive influence and significant between Organizational Commitment to Employee Job Satisfaction, and this calculated f value of 36.267 > f table of 3.16 it can be concluded that Organizational Support (X1) and Organizational Commitment (X2) have a significant effect on Employee Job Satisfaction (Y).